Cultura de tecidos em Gerbera - Nunes, Rita de Cássia Alves (2008)
Gerbera, from South Africa, belongs to Asteraceae family. They are herbaceous with flowers grouped in a head inflorescence. They are very popular and used as decorative garden plant, cut flowers and as experimental organism. São Paulo state leads the market of Brazilian ornamental flowers. Among the species produced by Brazilian companies, Gerbera is one of the very well accepted into the market. In the beginning XXth century micro propagation calls the attention of scientists; the pioneer was Haberlandt in 1902 with somatic cells. The studies on tissue culture, in Brazil, started at the 50´s in São Paulo Biological Institute. The chemical control of the differentiation of the aerial part was observed in culture of tobacco callus. This was the observation that the in vitro organogenesis process is controlled by hormonal substances that control the development in canopy, root or callus depending on the balance between auxins and cytokines. Some substances, even when in small amounts, delay or inhibit the substratum oxidation and can act at different levels on the oxidative sequence, these substances are called antioxidants. The living organisms possess natural scavenging mechanisms, enzymatically or not, of free radicals, not allowing their transformation in more toxic products for the cells. The enzyme superoxide dismutase, together with others is the main antioxidant defences that act in eukaryotic organisms.